Evaluation of Port-Angkar-Raas Ferry Transportation Tariffs Based on the Governor's Decree East Java Number 188/137/KPTS/013/2023 - Dzulfi, Isman; Hatina, Damaida; Kartini, Sri; Kelana, Sri; Rosyid, Muhammad Aqil (IWTJ : International Water Transport Journal, 2024)
Jangkar Ferry Port serves five ferry port. Of the five ferry, there is one ferry port that has experienced a change in pioneering status in the last five years, namely the Jangkar-Raas crossing served by KMP Dharma Kartika. The Jangkar-Raas crossing in 2019 to 2022 had pioneering status. However, starting in 2023, this crossing changed its status to a commercial crossing. In the first year of becoming a commercial crossing, revenue was not yet able to cover production costs. So at the end of 2023, the operator re-applied to be pioneered. After being evaluated by the regulatory team in 2024, this crossing was again granted pioneering status. Based on the calculations carried out, the average load factor was 69.82%. Referring to the applicable tariffs at the 2023 load factor conditions, the total income was obtained at IDR 2,896,681,000, while the Ship Operational Cost (BOK) was obtained at IDR 5,041,346,912, and the unit price per SUP per mile was obtained at IDR 746 at a load factor of 100%. Meanwhile, at a load factor of 60% it was IDR 1,243. At the existing tariff multiplied by the planned load factor, the income was obtained at IDR 3,959,890,194. The income that will be obtained when using the planned tariff and existing load factor is obtained at IDR 5,602,047,580, and at the load factor and planned tariff levels, the results were obtained at IDR 7,484,250,027.